Measuring long‐term disease control in atopic dermatitis: a validation study of well controlled weeks - Langan, Sinéad M.; Stuart, Beth; Bradshaw, Lucy; Schmitt, Jochen; Williams, Hywel C.; Thomas, Kim S. (Elsevier, 2017)
Background:Because atopic dermatitis (AD) is a relapsing, remitting disease, assessing long‐term control is important. Well controlled weeks (WCWs) have been used to assess asthma long‐term control, but never validated for AD. Objectives: To assess feasibility, validity and interpretability of WCWs in AD patients. Methods: Three studies of patients with moderate‐to‐severe AD including 4‐6 months of daily/weekly symptom and treatment use data were evaluated (Study A: n=336; Study B: n=60; Study C: n=224). WCWs were defined by worsening symptoms and increased medication use. Feasibility, construct validity and interpretability of WCWs were determined by assessing missing data, association with validated AD outcomes, and floor/ceiling effects. Analysis used linear and logistic regression. Results: WCWs were feasible to collect ‐ 95.2% (study A) and 94.7% (study B) contributed data for at least half of the weekly data‐points, and 93.2% and 88.7% contributed to all data‐points up to 4 months. WCWs were significantly associated with validated AD severity instruments including patient-reported (POEM) and objective signs (EASI, TIS and SASSAD). The odds of experiencing a WCW if AD severity was clear/mild was 5.8 (95% confidence interval (CI) 3.5 to 9.7), 1.9 (95%CI 0.8 to 4.4) and 8.1 (95%CI 4.5 to 14.6) in Studies A, B and C, respectively. WCWs were associated with ceiling effects‐ 31.6% (study A) and 37.5% (study B) of participants had no WCWs for >90% of the time. Conclusions: WCWs are valid and feasible for measuring long‐term control in AD trials. However, ceiling effects and burden of data collection may limit use.